2011
DOI: 10.1016/j.bbamem.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol regulates prokaryotic Kir channel by direct binding to channel protein

Abstract: Cholesterol is a major regulator of a variety of ion channels but the mechanisms underlying cholesterol sensitivity of ion channels are still poorly understood. The key question is whether cholesterol regulates ion channels by direct binding to the channel protein or by altering the physical environment of lipid bilayer. In this study, we provide the first direct evidence that cholesterol binds to prokaryotic Kir channels, KirBac1.1, and that cholesterol binding is essential for its regulatory effect. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 39 publications
4
43
1
Order By: Relevance
“…[13][14][15][16] However, in CCD cells, our data indicate that ROMK1 is not located in cholesterolrich lipid rafts but mainly, the planar regions of the apical membrane and that the cholesterol-lowering drug, lovastatin, does not alter ROMK1 channel activity in the CCD cells when PI(4)P5K I g expression is significantly reduced. These results suggest that the endogenous cholesterol levels in the planar regions, at least under resting conditions, are unable to reach the threshold that is required to directly inhibit ROMK1 channels but indirectly regulate ROMK1 channels through PI(4)P5K.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[13][14][15][16] However, in CCD cells, our data indicate that ROMK1 is not located in cholesterolrich lipid rafts but mainly, the planar regions of the apical membrane and that the cholesterol-lowering drug, lovastatin, does not alter ROMK1 channel activity in the CCD cells when PI(4)P5K I g expression is significantly reduced. These results suggest that the endogenous cholesterol levels in the planar regions, at least under resting conditions, are unable to reach the threshold that is required to directly inhibit ROMK1 channels but indirectly regulate ROMK1 channels through PI(4)P5K.…”
Section: Discussionmentioning
confidence: 47%
“…[13][14][15][16] However, the evidence came from either cell overexpression models or artificial bilayer membranes. Because endogenous cholesterol, especially in epithelial cells, is usually strongly associated with sphingolipids through hydrogen bonds in the cell membrane to form lipid rafts, 18 it remains unclear whether the endogenous cholesterol could reach and interact with the cytosolic pore of Kir channels, although the exogenously added cholesterol can.…”
mentioning
confidence: 99%
“…Differential effects of cholesterol analogues on channel function were also demonstrated in several other types of ion channels, including the nicotinic acetylcholine receptor (19), BK channels (20), and TRPV1 channels (21). Most recently, our laboratory has shown that cholesterol binds to purified KirBac1.1 channels and that cholesterol-KirBac1.1 binding is essential for the inhibitory effect of cholesterol on channel activity (22).…”
mentioning
confidence: 99%
“…In general three different mechanisms may be involved in regulation of ion channels by cholesterol: (i) specific interactions (ii) changes in the physical properties of the membrane bilayer and (iii) maintaining the scaffolds for protein-protein interactions. Furthermore, our recent data for the first time demonstrate a specific cholesterol-channel binding (Singh et al, 2011). One possibility is that cholesterol may interact directly and specifically with the transmembrane domains of the channels protein.…”
Section: Cholesterol and Ion Channelsmentioning
confidence: 99%
“…Clearly, therefore, more than one mechanism has to be involved in cholesterol-induced regulation of different ion channels. Studies from our laboratory have shown that many major and important ion channels are regulated by changes in the level of membrane cholesterol (Epshtein et al, 2009;Levitan, 2009;Levitan et al, 2010;Rosenhouse-Dantsker et al, 2011;Singh et al, 2009b;Singh et al, 2011). In general three different mechanisms may be involved in regulation of ion channels by cholesterol: (i) specific interactions (ii) changes in the physical properties of the membrane bilayer and (iii) maintaining the scaffolds for protein-protein interactions.…”
Section: Cholesterol and Ion Channelsmentioning
confidence: 99%